Investigation of thermal conductivity and thermal resistance analysis on different combination of natural fiber composites of Banana, Pineapple and Jute. (2020) - Muthukumar, K.; Sabariraj, R.V.; Dinesh Kumar, S.; Sathish, T.
Abstract: Banana, Pineapple and Jute fiber were mixed with different combination of volume percentage by hand layup technique. For this investigation six types of combinations used. Banana fiber has 60% in all the combination and remaining 40% of fiber only shared with Pineapple fiber and Jute fiber for six different combinations and also each combination with three different (5 mm, 10 mm and 15 mm) thicknesses. The corresponding thermal analysis such as thermal conductivity and thermal resistance of six combination fiber composites were compared for the good thermal insulator for insulation applications.